Twin Ball and Twin Cylinder of Wave Energy - Dwikki Syachruluddin; Arfena Deah Lestari; Muhammad Ivanto; Mochammad Meddy Danial; Jasisca Meirany (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Twin Ball and Twin Cylinder of Wave Energy have the working principle of converting kinetic energy into electrical energy. The problem that occurs in Sungai Raya Kepulauan Sub-district is the problem of limited electricity supply in the ocean area in Lemukutan Island Village, where the electricity demand in the village is limited. The electricity supplied is PLN electricity from diesel power plants that still use fossil fuel sources. This study aims to determine the potential of ocean wave energy that can be utilized by fishermen. This research method uses quantitative methods using secondary data in the form of significant wave height and period data obtained from the ECMWV website. The results of the Twin ball analysis use a ball buoy with a diameter of 18 cm, while Twin Cylinder uses a tube buoy with a diameter of 15 cm and a height of 16 cm. The arm length of both types of floats is 30 cm. Comparison of scale 1:700 Twin Ball and Twin Cylinder can produce electricity of 334.18 W and 106.93 W. From the above results, it can be seen that Twin Ball can produce more power than Twin Cylinder. The amount of power generated can help 1 fisherman's began for lighting needs. About 3 - 4 lamps with a power of 50 W to 75 W per 1 lamp can be used as lighting.